drwls

posted by .

My previous question:
Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity.

(secx/sinx)*(cotx/cscx)
= (secx/cscx)(cotx/sinx)
= (sinx/cosx)*cotx*(1/sinx)

"The last steps should be obvious"

Not to me. I can convert (sinx/cosx) to tanx if that's even what I'm suppose to do. Is (sinx/cosx)*cotx*(1/sinx) the answer?

• drwls -

I am not sure he is still here

(sinx/cosx)*cotx*(1/sinx)
(sin/cos)*(cos/sin) * (csc)

1 * (csc) = csc

remember csc = 1/sin

• drwls -

I skipped that step that tanx*cotx = 1

Similar Questions

1. Math

Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If you square this you have (1-cosX)^2/(sinX)^2 Now use (sinX)^2 = 1 - (cosX)^2 to get (1-cosX)^2 / 1 - …
2. calculus

express in sinx 1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so what do i do w. that extra one on the top!?
3. trig

express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
4. Pre-Calculus

Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2
5. Trig Help

Prove the following: [1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)] =[sinx+sin^2x]/[sinx+1] =[sinx+(1-cos^2x)]/[sinx+1] =?
6. Math

Im really struggling with these proving identities problems can somebody please show me how to do these?
7. Math

Im really struggling with these proving identities problems can somebody please show me how to do these?
8. Math

I'm only aloud to manipulate one side of the problem and the end result has to match the other side of the equation Problem 1. sinx + cosx + sinx + tanx + cosxcotx = secx + cscx Problem 2. ((sinx + cosx)/(1 + tanx))^2 + ((sinx - cos^2x)/(1 …
9. trigonometry

can i use factoring to simplify this trig identity?
10. Precalculus/Trig

I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …

More Similar Questions